Lời giải:
a) \(m=2\) thì (1) trở thành:
\(3x^2+4x-4=0\)
\(\Leftrightarrow (3x-2)(x+2)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{3}\\x=-2\end{matrix}\right.\)
b) Ta có:
\(x^2-2x+1=0\Leftrightarrow (x-1)^2=0\Leftrightarrow x-1=0\Leftrightarrow x=1\)
Do đó để (1) và \(x^2-2x+1=0\) thì (1) phải có nghiệm \(x=1\)
Suy ra \(3.1^2+4(m-1).1-m^2=0\)
\(\Leftrightarrow -m^2+4m-1=0\)
\(\Leftrightarrow m=2\pm \sqrt{3}\)
c)
Xét \(\Delta'=[2(m-1)]^2+3m^2=7m^2-8m+4\)
\(=7(m-\frac{4}{7})^2+\frac{12}{7}\)
Thấy rằng \((m-\frac{4}{7})^2\geq 0\forall m\in\mathbb{R}\Rightarrow \Delta'\geq \frac{12}{7}>0\) với mọi số thực m
\(\Rightarrow (1)\) luôn có hai nghiệm phân biệt (đpcm)